Sex Crime in the News - Soothill Keith; Walby Sylvia (Rouledge, 1991)
List of Illustrations, Acknowledgements, Introduction, The Newspaper Studies, Seeking Out the Sex Field, Sex Crime in Court, Sex Offenders After Conviction, Informing the Public, Changing Legal Practice, Conclusion, Notes, Name and Subject Index.